(untitled) (The Lumbini Journal of Business and Economics, 2025)
Purpose: This study examines the relationship between emotional intelligence (EI), job satisfaction (JS), and organizational citizenship behavior (OCB) among employees in Nepalese commercial banks. The study also analyzes the role of job satisfaction as a mediating influence in this relationship, aiming to understand presence of emotional intelligence among employees’ impact on positive organizational citizenship behavior through increased job satisfaction. Methods: The study employed a quantitative approach with descriptive and causal research designs to achieve objectives of the study. Data were collected from 408 respondents using a purposive sampling method through an online survey. The study variables were measured by using a five-point Likert scale, and the collected data were analyzed by SPSS version 26.0 and AMOS Graphics. Results: The findings reveal a strong positive relationship between emotional intelligence and organizational citizenship behavior, suggesting that employees with higher EI are more likely to engage in supportive and voluntary behaviors that benefit their organization. Although the direct relationship between emotional intelligence and job satisfaction was not statistically significant, the mediation analysis showed that job satisfaction fully mediates the relationship between emotional intelligence and organizational citizenship behavior. This suggests that EI influences OCB indirectly through subtle psychological or contextual processes reflected in job satisfaction. Conclusion: The study concludes that EI positively influences organizational citizenship behavior (OCB) through its impact on job satisfaction JS. While EI does not directly affect JS, it indirectly develops OCB by enhancing job satisfaction. Job satisfaction plays a full mediating role in the relationship between EI and OCB, with a significant indirect effect of EI on OCB through job satisfaction. These findings emphasize the need to focus on emotional intelligence and job satisfaction to encourage positive behaviors in the workplace.